помогите пожалуйста решить уравнения:

3(x+6)=2(x-3)

9(x-3)=5(x+5)

2(2-y)=y-5

-(4x-2)=-6

-(3x-4)=3x-8

3(x-5)=x+3

-2(x+3)=2x-1

-(3x-4)=3x-8

2

Ответы и объяснения

2013-03-30T01:04:25+04:00

9(x-3)=5(x+5)    

9х-27=5х+25

9х-5х=25+27

4х=52

х=13

 

-(4x-2)=-6    

4х-2=6

4х=6+2=8

х=2

 

-(3x-4)=3x-8

3х-4=-3х+8

3х+3х=4+8

6х=12

х=2

 

3(x-5)=x+3

3х+15-х-3=0

2х+12=0

2х=-12

х=-6

 

-(3x-4)=3x-8

3х-4=-3х+8

3х-4+3х-8=0

6х-12=0

6х=12

х=2

 

-2(x+3)=2x-1

-2х-6=2х-1

-2х-2х-6+1=0

-4х-5=0

-4х=5

х=1,25

2013-03-30T01:30:07+04:00

3(х+6)=2(х-3)

3х+18=2х-6

3х-2х=-18-6

х= -24

 

9(х-3)=5(х+5)

9х-27=5х+25

9х-5х=25+27

4х=52

х=13

 

2(2-у)=у-5

4-2у=у-5

-2у-у=-4-5

3у=9

у=3

 

 

-(4х-2)=-6

-4х+2=-6

-4х=-6-2

4х=8

х=2

 

 

-(3х-4)=3х-8

-3х+4=3х-8

-3х-3х=-8-4

6х=12

х=2

 

 

3(х-5)=х+3

3х-15=х+3

3х-х=3+15

2х=18

х=9

 

 

-2(х+3)=2х-1

-2х-6=2х-1

-2х-2х=-1+6

-4х=5

х=-1,25

 

-(3х-4)=3х-8

-3х+4=3х-8

-3х-3х=-8-4

6х=12

х=2